Diversity of Colombian passifloraceae : Biogeography and an updated list for conservation - Ocampo Pérez, John A.; Coppens d'Eeckenbrugge, Geo; Restrepo, M; Jarvis, Andy; Salazar, M.; Caetano, C.M. (2007)
The list of Colombian Passifloraceae was revised, using 3.930 records from literature, herbaria, and field observations. It includes 167 species, 165 of them native, which is equivalent to 27% of the family. Our list includes more details on species distribution and presents 26 species new to Colombia. Passiflora is the most important genus, with 162 species, whose center of diversity is in the Ecuadorian and Colombian Andes. Inside Colombia, the highest diversity is concentrated in the Andean region, which houses 81% of the species, particularly in the departments of Antioquia, Valle del Cauca, Cundinamarca, Quindío, Risaralda, and Caldas. The highest number of species is found at between 1000 and 2000 m above sea level and the most common thrive in disturbed habitats, such as roadsides, cultivated plots, and secondary forests. Most of the 58 endemic species are found at between 1500 to 2500 m and belong mainly to subgenera Tacsonia and Decaloba. Forty-two species produce an edible fruit, and nine are commercially cultivated. Among the species reported, 70% are threatened to some degree and three are considered extinct. Colombia may still house many unknown species in poorly explored departments, but more information about Passiflora diversity and distribution is needed to develop its economic potential. The conservation of this threatened species along with its habitat is essential and urgent. Because of the species' multiple ecological interactions with many organisms, both aspects can be combined using Passifloraceae as an indicator of biodiversity in the Andean region.